Beneficial Effect of Fenofibrate and Silymarin on Hepatic Steatosis and Gene Expression of Lipogenic and Cytochrome P450 Enzymes in Non-Obese Hereditary Hypertriglyceridemic Rats - Vecera, Rostislav; Poruba, Martin; Hüttl, Martina; Malinska, Hana; Oliyarnyk, Olena; Markova, Irena; Racova, Zuzana; Soukop, Jan; Kazdova, Ludmila (Current issues in molecular biology, 2022)
The efficacy of fenofibrate in the treatment of hepatic steatosis has not been clearly demonstrated. In this study, we investigated the effects of fenofibrate and silymarin, administered as monotherapy and in combination to existing hepatic steatosis in a unique strain of hereditary hypertriglyceridemic rats (HHTg), a non-obese model of metabolic syndrome. HHTg rats were fed a standard diet without or with fenofibrate (100 mg/kg b.wt./day) or with silymarin (1%) or with a combination of fenofibrate with silymarin for four weeks. Fenofibrate alone and in combination with silymarin decreased serum and liver triglycerides and cholesterol and increased HDL cholesterol. These effects were associated with the decreased gene expression of enzymes involved in lipid synthesis and transport, while enzymes of lipid conversion were upregulated. The combination treatment had a beneficial effect on the gene expression of hepatic cytochrome P450 (CYP) enzymes. The expression of the CYP2E1 enzyme, which is source of hepatic reactive oxygen species, was reduced. In addition, fenofibrate-induced increased CYP4A1 expression was decreased, suggesting a reduction in the pro-inflammatory effects of fenofibrate. These results show high efficacy and mechanisms of action of the combination of fenofibrate with silymarin in treating hepatic steatosis and indicate the possibility of protection against disorders in which oxidative stress and inflammation are involved.
Keywords: CYP 4A1; triglycerides; fenofibrate; CYP 2E1; liver; silymarin; NAFLD; lipoperoxidation